The Cover of the Holy Building, the Symbol of Politics: The Historical Power Rivalry over the Kiswa of the Ka‘ba - Atmaca, Esra (Religions, 2025)
For Muslims, the Ka‘ba holds immense significance as the destination of pilgrimage—an obligatory act of worship—and as the direction toward which prayers are performed. The kiswa is a cover that has been placed on the Ka‘ba, the holiest place in Islam, since the Jāhiliyya period as an expression of respect for it. Although there are some exceptions in Islamic history, it is usually changed once a year and it was woven in different colours according to the period, and finally it became a tradition to be black. The kiswa of the Ka‘ba is one of the most important religious and political symbols of Islamic history. This article analyses the role of the kiswa of the Ka‘ba in the relations between Muslim rulers in the Islamic world throughout history. From the earliest periods of Islam, the kiswa has been recognized as a symbol of legitimacy and a means of asserting control over the administration of pilgrimage. Many states, such as the Abbāsids, Mamlūks, and Ottomans, expressed or reinforced their political legitimacy among Muslims by showing their influence over the Ka‘ba through the tradition of the kiswa. In the medieval Islamic world, Muslim states or local administrators of these states especially used the kiswa as a symbol of sovereignty, thus increasing their influence in the regions they governed. Some Muslim administrators who wanted to send the kiswa to the Ka‘ba competed with each other or prevented the other from sending the kiswa to the Ka‘ba because each year only one kiswa was sent to Mecca. In this study, the position of the kiswa as a political symbol in the quest for the legitimacy of Muslim rulers in Islamic history and the historical development of this issue are discussed and analysed with examples.